Organization of Students’ Self-Government as an Important Condition of Organizational Capabilities of the Future Teachers Formation - Ludmila Brovchak (Pedagogical Discourse, 2012)
The article deals with the peculiarities of the students’ self-government in higher educational institutions. The value of students’ self-government as a condition of organizational capabilities of future teachers are analyzed and grounded